Allah's zoo - Khan, Nafees (Goodword Books India, 2011)
"Allah's Zoo" is a poignant exploration of faith, identity, and the human experience, framed through the lens of a zoo where animals represent different cultures and beliefs. The narrative weaves together personal stories that highlight the interconnectedness of humanity and the search for understanding amidst diversity.